Trade policy uncertainty and its effect on foreign direct investment: Evidence from Mexico - Alfonso Cebreros; Alejandrina Salcedo; Daniel Chiquiar; Aldo Heffner-Rodríguez (Banco de México, 2020)
This paper investigates whether "trade policy uncertainty" (TPU), even absent changes in actual policy, may have an adverse effect on foreign direct investment. The paper focuses on the case of Mexico, where we observe a plausibly sharp and exogenous increase in TPU vis-à-vis a large trading partner beginning in the second half of 2016. To test this hypothesis, we use data from Google Trends to construct a TPU index and argue that this index adequately captures both time series and cross-sectional variation in TPU across states in Mexico. We exploit this variation to identify the effect of increased uncertainty on FDI flows. We find that the increase in TPU was associated with a negative effect on FDI inflows, with the effect being driven by the negative impact that TPU had on FDI in export oriented states.
Keywords: F40; F62; F21; 330; trade policy uncertainty; foreign direct investment; real options